THE IMPACT OF MIGRATION POLICY ON THE NATIONAL SECURITY OF THE KYRGYZ REPUBLIC: CHALLENGES, STRATEGIES AND PROSPECTS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the impact of migration policy on the national security of the Kyrgyz Republic in the context of globalization, cross-border mobility and growing transnational threats. The analysis of the key challenges faced by the state in the field of migration regulation, including the growth of illegal migration, the threat of radicalization, economic marginalization and institutional vulnerability. Special attention is paid to the institutionalization of migration management, digital transformation and international cooperation within the framework of the EAEU, SCO and the Almaty process. It is shown that the migration policy of the Kyrgyz Republic is developing towards the integration of strategic planning mechanisms, risk management and the use of digital monitoring and forecasting tools. A systematization of the interrelationships between migration processes and components of national security in the form of an analytical table is proposed. The conclusion is made about the need to further strengthen the adaptive, preventive and interagency coordinated approach in the migration policy of the Kyrgyz Republic.
Keywords: migration policy, national security, Kyrgyzstan, digitalization, transnational threats, EAEU, SCO, Almaty process, risk-based management, strategic planning.